2002
DOI: 10.1161/01.hyp.0000036399.80194.d8
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Antagonist Improves Diastolic Function in Essential Hypertension

Abstract: Abstract-Experimental studies demonstrated that mineralocorticoid antagonists prevent or reverse myocardial fibrosis.Therefore, we tested the hypothesis that the aldosterone antagonist canrenone can improve left ventricular diastolic function in essential hypertension. Using digitized M-mode echocardiography and 24-hour blood pressure monitoring (ABPM), we realized a prospective, randomized, controlled study on 34 never-treated essential hypertensives with left ventricular diastolic dysfunction. Echocardiogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 38 publications
2
41
0
2
Order By: Relevance
“…An inverse relationship of plasma aldosterone with E/A ratio was initially reported in treated patients with hypertension and LV hypertrophy 13 and improvement of diastolic function associated with reduction of LV mass was obtained with spironolactone in hypertensive patients with LV hypertrophy who were already treated with angiotensinconverting enzyme inhibitors and calcium-channel blockers. 30 Conversely, a recent study of hypertensive patients with preclinical LV diastolic dysfunction has reported no change of E/A ratio and diastolic function assessed by MRI after addition of spironolactone to previous antihypertensive treatment, despite significant reduction in LV mass.…”
Section: Discussionmentioning
confidence: 96%
“…An inverse relationship of plasma aldosterone with E/A ratio was initially reported in treated patients with hypertension and LV hypertrophy 13 and improvement of diastolic function associated with reduction of LV mass was obtained with spironolactone in hypertensive patients with LV hypertrophy who were already treated with angiotensinconverting enzyme inhibitors and calcium-channel blockers. 30 Conversely, a recent study of hypertensive patients with preclinical LV diastolic dysfunction has reported no change of E/A ratio and diastolic function assessed by MRI after addition of spironolactone to previous antihypertensive treatment, despite significant reduction in LV mass.…”
Section: Discussionmentioning
confidence: 96%
“…In essential hypertension, a low dose of the aldosterone antagonist canrenone added to antihypertensive treatment has been shown significantly to improve left ventricular diastolic function [94]. This improvement, not accounted for by changes in blood pressure and left ventricular mass, can be ascribed to a direct action of the drug on the myocardium.…”
Section: Interaction With Aldosteronementioning
confidence: 99%
“…Med Clin N Am 88 (2004) [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Under certain circumstances, a regression of fibrous tissue occurs after the repair process has been completed. This is related to fibrillar collagen degradation by matrix metalloproteinases [19,20].…”
mentioning
confidence: 99%
“…Furthermore, MRAs have been shown to improve CV outcomes in subjects with HFREF 15, 16, 17, 18, 19. Several studies have evaluated the efficacy and safety of MRAs in patients with asymptomatic LVDD20, 21, 22, 23, 24 as well as established HFPEF 25, 26, 27, 28, 29, 30…”
mentioning
confidence: 99%